Determination of veterinary antibiotics in bovine urine by liquid chromatography–tandem mass spectrometry. (15th October 2015) - Chiesa, Luca; Nobile, Maria; Arioli, Francesco; Britti, Domenico; Trutic, Natasa; Pavlovic, Radmila; Panseri, Sara
Highlights: Analysis of antibiotics in bovine urine, as a non-invasive matrix, is convenient. Antibiotics presence in bovine urine might be considered as an environmental risk. Multiclass HPLC–MS/MS method for antibiotics assay in bovine urine was validated. Majority of samples enrolled in this study were positive on tetracyclines. It is crucial to screen antibiotics in bovine urine before processing in food industry. Abstract: A follow-up of antibiotics (tetracyclines, fluoroquinolones, cephalosporins, penicillins and amphenicols) in the bovine urine is important for two reasons: to understand if they are still present in organism, and whether their occurrence in urine might be considered as an environmental risk. A validated HPLC–MS/MS method (Decision 2002/657/EC) for antibiotics determination in bovine urine was developed. CCα and CCβ were in the range of 0.58–0.83 and 0.55–1.1 ng mL −1, respectively. Recoveries were 92–108%, with inter-day repeatability below 12%. Analysis of bovine urine revealed frequent presence of tetracyclines, which was related with animal's age. The cause, most presumably, might be found in different therapeutic protocols applied for veal calves and young bulls enrolled in this study. Most abundant was oxytetracycline with highest level in veal calves (1718 ng mL −1 ) vs. young bulls (2.8 ng mL −1 ). Our results indicate the necessity of antibiotics monitoring in bovine urine before animals undergo further processing in the food industry.